Astrocyte-like glia in the peripheral nervous system: an immunohistochemical study of enteric glia - Jessen, KR (J Neurosci, 1983)
The similarities between the enteric nervous system of the gut and the central nervous system (CNS), both of which function as complex integrative nervous networks, include striking ultrastructural similarities between the glia of the enteric nervous system and the astrocytic glia of the CNS. In this paper we have determined whether this anatomical resemblance also extends to the molecular level by examining the enteric glial cells to see whether they express several surface and intracellular molecules which are highly restricted to glia and to astrocytes in particular. Indirect immunofluorescence was used to visualize the antigens in frozen sections of gut wall and in whole mount, tissue culture, and freshly dissected preparations of myenteric and submucous plexuses from rats of various ages. It was found that enteric glial cells expressed the intracellular proteins glial fibrillary acidic protein, glutamine synthetase, and vimentin both in situ and in culture. The surface antigen Ran-2 was expressed in situ but not in culture, and the surface antigen Ran-1 was expressed in culture but not in situ. Cultured enteric glial cells did not express fibronectin in significant quantity, nor did they make galactocerebroside. From these results we conclude that the adult phenotype of enteric glia in situ closely resembles that of astrocytes, while in culture some of their cell surface features change, reverting to those seen during development. Because these cells possess distinctive molecular features and numerically form one of the major populations of peripheral glia, it is appropriate to classify them as a third distinctive category of peripheral glial cells, in addition to satellite and Schwann cells. The molecular similarities between these cells and astrocytes, in addition to their anatomical resemblance, suggest that a further study of enteric glia will provide new insights into the role of glia in integrative nervous tissues.